DNA damage-induced degradation of Cdc25A does not lead to inhibition of Cdk2 activity in mouse embryonic stem cells - Koledova, Zuzana; Kafkova, Leona Raskova; Krämer, Alwin; Divoky, Vladimir (Stem cells (Dayton, Ohio), 2010)
Cyclin-dependent kinase two (Cdk2) is the major regulator of the G1/S transition and the target of an activated G1 checkpoint in somatic cells. In the presence of DNA damage, Cdk2 kinase activity is abrogated by a deficiency of Cdc25A phosphatase, which is marked by Chk1/Chk2 for proteasomal degradation. Embryonic stem cells (ESCs) lack a G1 checkpoint response. In this study, we analyzed the G1 checkpoint pathways in mouse ESCs (mESCs) in the presence of DNA double-strand breaks evoked by ionizing radiation (IR). We show that checkpoint pathways, which operate during G1 phase in somatic cells, are activated in mESCs after IR; however, Cdk2 activity is not abolished. We demonstrate that Cdc25A is degraded in mESCs, but this degradation is not regulated by Chk1 and Chk2 kinases because they are sequestered to the centrosome. Instead, Cdc25A degradation is governed by glycogen synthase kinase-3beta kinase. We hypothesize that Cdc25A degradation does not inhibit Cdk2 activity because a considerable proportion of Cdk2 molecules localize to the cytoplasm and centrosomes in mESCs, where they may be sheltered from regulation by nuclear Cdc25A. Finally, we show that a high Cdk2 activity, which is irresponsive to DNA damage, is the driving force of the rapid escape of mESCs from G1 phase after DNA damage.
Keywords: oprava DNA; aktivace enzymů; Animals; DNA Damage; buněčné linie; Radiation, Ionizing; Genes, cdc; Enzyme Activation; Cell Cycle; Checkpoint Kinase 1; DNA; centrozom; fosfatasy cdc25; Checkpoint Kinase 2; proteinkinasy; Mice; Protein Serine-Threonine Kinases; signální transdukce; DNA Repair; checkpoint kinasa 1; Glycogen Synthase Kinase 3 beta; myši; Signal Transduction; ionizující záření; checkpoint kinasa 2; Cell Line; buněčný cyklus; G1 fáze; cyklin-dependentní kinasa 2; poškození DNA; embryonální kmenové buňky; Centrosome; cdc25 Phosphatases; kinasa glykogensynthasy 3beta; Cytoplasm; G1 Phase; Protein Kinases; kinasa 3 glykogensynthasy; zvířata; Cyclin-Dependent Kinase 2; Glycogen Synthase Kinase 3; CDC geny; protein-serin-threoninkinasy; cytoplazma; Embryonic Stem Cells